Positive Aspects of Oxidative Stress at Different Levels of the Human Body: A Review - George Jîtcă; Bianca E. Ősz; Amelia Tero-Vescan; Amalia Pușcaș Miklos; Carmen-Maria Rusz; Mădălina-Georgiana Bătrînu; Camil E. Vari (MDPI AG, 2022)
Oxidative stress is the subject of numerous studies, most of them focusing on the negative effects exerted at both molecular and cellular levels, ignoring the possible benefits of free radicals. More and more people admit to having heard of the term "oxidative stress", but few of them understand the meaning of it. We summarized and analyzed the published literature data in order to emphasize the importance and adaptation mechanisms of basal oxidative stress. This review aims to provide an overview of the mechanisms underlying the positive effects of oxidative stress, highlighting these effects, as well as the risks for the population consuming higher doses than the recommended daily intake of antioxidants. The biological dose-response curve in oxidative stress is unpredictable as reactive species are clearly responsible for cellular degradation, whereas antioxidant therapies can alleviate senescence by maintaining redox balance; nevertheless, excessive doses of the latter can modify the redox balance of the cell, leading to a negative outcome. It can be stated that the presence of oxidative status or oxidative stress is a physiological condition with well-defined roles, yet these have been insufficiently researched and explored. The involvement of reactive oxygen species in the pathophysiology of some associated diseases is well-known and the involvement of antioxidant therapies in the processes of senescence, apoptosis, autophagy, and the maintenance of cellular homeostasis cannot be denied. All data in this review support the idea that oxidative stress is an undesirable phenomenon in high and long-term concentrations, but regular exposure is consistent with the hormetic theory.